A Rare Case of Extramedullary T/Myeloid Mixed Phenotype Acute Leukemia with t(1;5)(q23;q33). (26th December 2016) - Monabati, Ahmad; Safaei, Akbar; Nouri, Sadat; Safavi, Moeinadin; Solhjoo, Freidoon
Abstract : Mixed phenotype acute leukemia (MPAL) is a rare neoplasm which accounts for 2–5% of all leukemias and it is classified under heading of acute leukemia of ambiguous lineage in 2008 WHO classification. This patient was a 61-year-old man who presented with malaise and weakness. In physical examination there was cervical and axillary lymphadenopathy. Paraclinical evaluation revealed anemia (Hb = 10.3 g/dL, MCV = 108 fl). Histologic sections of the axillary lymph node revealed leukemic involvement with two discrete populations of cells in immunohistochemistry. One population was immunoreactive for MPO and the other showed immunostaining for CD3, CD99, and tdt. Differential count of bone marrow cells in marrow aspirate had 6% blast. Karyotype study on bone marrow culture depicted an interesting finding which was t(1;5)(q23;q33). An extensive search on literature was done for the same genetic change. A similar translocation has been mentioned in literature for other hematologic malignancies but not for same neoplasm; anyhow this translocation was an imbalanced one and led to der(5)t(1;5)(q12-25;q13-q35).